LITERATUR REVIEW: FITOTERAPI UNTUK MENINGKATKAN SISTEM IMUN - Nawwar Irfan; Citra Aulia Restu; Jesika Sinaga; Syukron Jauhary; Yunita Lumban Raja (PT. Saha Kreasi Indonesia, 2026)
The immune system serves as the primary defense mechanism against pathogenic agents and plays an essential role in maintaining physiological homeostasis. Impairment of immune function may increase susceptibility to infections and adversely affect overall health. Phytotherapy, which involves the use of medicinal plants as therapeutic agents, has been increasingly explored as a natural immunomodulatory approach due to its favorable safety profile and abundant availability in Indonesia. This article aims to evaluate the potential of phytotherapy in enhancing immune function based on existing scientific evidence. A literature review was conducted involving 20 national and international scientific articles retrieved from PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda databases. The reviewed articles included in vitro, in vivo, in silico, clinical studies, and community-based research addressing the immunomodulatory effects of medicinal plants. The findings indicate that 18 medicinal plant species have been reported to exhibit immunomodulatory activity, with the most extensively studied plants being Phyllanthus niruri, Zingiber officinale, Curcuma longa, Curcuma xanthorrhiza, and Nigella sativa. The immunomodulatory effects are mediated through enhanced macrophage phagocytic activity, stimulation of lymphocyte proliferation, activation of natural killer cells, and regulation of cytokine production, including IL-2, IL-6, IL-12, IFN-γ, and TNF-α. These biological activities are associated with the presence of bioactive compounds such as flavonoids, alkaloids, polysaccharides, terpenoids, and phenolic compounds. In conclusion, phytotherapy demonstrates considerable potential as a natural immunomodulator; however, further standardization of raw materials, formulation processes, and well-designed clinical trials are required to support its development into evidence-based phytopharmaceuticals.